The emerging role of pre-messenger RNA splicing in stress responses: Sending alternative messages and silent messengers - Dutertre, Martin; Sanchez, Gabriel; Barbier, Jérôme; Corcos, Laurent; Auboeuf, Didier (RNA biology, 2011)
Alternative splicing (AS) of pre-messenger RNAs is a major process contributing to both transcriptome and proteome diversity in various physiological and pathological situations. There is also accumulating evidence that various stresses impact on AS. In particular, recent analyses of the transcriptome reveal large numbers of AS events that are regulated by genotoxic stress inducers like radiations and chemotherapeutic agents. Many AS events have the potential to affect the relative production of protein isoforms with different activities, as shown in the case of several genes involved in apoptosis. There is also increasing evidence that stresses induce "non-productive" splice variants, leading to a decrease in gene expression levels or preventing increases in protein levels despite transcriptional stimulation. This is typically achieved by the production of splice variants that are subject to nonsense-mediated decay. In addition, recent studies suggest that pre-mRNA splicing efficiency or fidelity may be altered by stresses. For example, various genotoxic agents induce multiple exon skipping in MDM2 transcripts, thereby preventing the production of the main p53-ubiquitin ligase and favoring p53 activity in response to genotoxic agents. In terms of mechanisms, stresses can impact on pre-mRNA splicing by inducing post-translational modifications and subcellular redistribution of splicing factors, or by targeting the communication between the splicing and transcription machineries. Altogether, these data suggest that splicing regulatory networks play a key role in the cellular responses triggered by stresses.